2011
DOI: 10.1534/genetics.111.129940
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of the Neural Substrates for Sexual Behaviors in Drosophila melanogaster

Abstract: The male-specific Fruitless proteins (FruM) act to establish the potential for male courtship behavior in Drosophila melanogaster and are expressed in small groups of neurons throughout the nervous system. We screened ∼1000 GAL4 lines, using assays for general courtship, male–male interactions, and male fertility to determine the phenotypes resulting from the GAL4-driven inhibition of FruM expression in subsets of these neurons. A battery of secondary assays showed that the phenotypic classes of GAL4 lines cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…Flies were anesthetized by CO 2 , introduced into a humidified courtship chamber divided by a plastic film to separate experimental from target flies, and allowed to recover at rearing temperature for 3–4 hours prior to testing, as described before (Manoli et al, 2005; Meissner et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Flies were anesthetized by CO 2 , introduced into a humidified courtship chamber divided by a plastic film to separate experimental from target flies, and allowed to recover at rearing temperature for 3–4 hours prior to testing, as described before (Manoli et al, 2005; Meissner et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The FruM-positive median bundle neurons were shown to be critical for correct behavioral sequence generation using RNAi against FruM (Manoli and Baker, 2004). A screen using the intersection between FruM and GAL4 neuronal expression facilitated identification of additional brain regions involved in male courtship (Meissner et al, 2011). Statistical analysis of courtship behavior when randomly generated subsets of the FruM expression pattern were feminized or inhibited suggested brain regions key for courtship initiation (Kimura et al, 2008).…”
Section: : En Route To the Courtship Circuitmentioning
confidence: 99%
“…As proof of principle, we demonstrated that a previously identified subset of the fruitless (fru)-expressing neurons involved in courtship song are all produced in hemilineage 12A and cleanly isolated this fru+ cluster. The fru-expressing neurons are necessary and sufficient to drive most aspects of male courtship behavior, and their anatomy, genetics, and function have been dissected in detail (e.g., Manoli and Baker, 2004;Yu et al, 2010b;Meissner et al, 2011). The fru expression pattern can be divided into ∼100 groups of cells, including ∼40 in the VNS (Yu et al, 2010).…”
Section: Using Hemilineage Lines To Target Behaviorally-relevant Groumentioning
confidence: 99%